The impact of movement control order on rural livelihood in Malaysia - Hassan, Mohd Azren; Anuar Zabidi, Nur Atiqah; Ramli, Hidayati; Muthuveeran, Adam Aruldewan S.; Abdullah, Yusfida Ayu (UiTM Press, 2022)
In 2020, the spread of Coronavirus (COVID-19) had a global impact on normal daily life. The Government of Malaysia officially declared the Movement Control Order (MCO), an official national lockdown, to reduce the virus’s spread. In the face of the unprecedented global health pandemic, Malaysia had struggled to protect its citizens’ welfare and livelihoods, particularly in the hardest-hit rural areas. Therefore, this study uses the sustainable livelihood approach (SLA) focusing on the aspect of financial assets and government intervention to enhance understanding on the vulnerability in rural area’s livelihood. Pasir Puteh, Kelantan was identified as the rural area for this study. The analysis was performed on a questionnaire survey based on convenience sampling of 62 respondents. Cross table analysis and a correlation test were used to examine the livelihood of the rural area concerning the financial assets, government intervention and vulnerability. The findings indicated that the MCO had a substantial impact on the rural area regarding the vulnerability toward the financial assets, such as employment status, job loss, increasing living costs, and an insufficient response to rural economic challenges. At the same time, there is no substantial government intervention in the welfare of rural areas. According to the results, the study concluded that the government should set up training courses to assist in the long-term recovery of rural areas due to the enforced lockdown, which has adversely affected rural livelihoods.